Evaluation of the genetic variability of homoeologous group 3 SSRs in bread wheat - Chebotar, S.; Sourdille, P.; Paux, E.; Balfourier, F.; Feuillet, C.; Bernard, M. (Цитология и генетика, 2009)
Thorough characterization of the genetic variability in bread wheat (Triticum aestivum L.) is important for a better improvement of this key crop and to increase cereal yield in the context of sustainable agriculture to face human needs in the next decades. To study the genetic variability of SSRs on wheat homoeologous group 3 chromosomes, we characterized 38 hexaploid and two tetraploid wheat lines using a set of 165 microsatellites that we cytogenetically assigned to the 17 deletion bins for chromosomes group 3. Изучали вариабельность МС-локусов третьей гомеологичной группы хромосом T. aestivum L., осуществили сопоставление изменчивости микросателлитов в дистальных и проксимальных областях хромосом и физическое картирование МС-локусов с помощью делеционных, дителосомных, нуллитетрасомных линий и провели сравнительный анализ вариабельности микросателлитных локусов хромосом 3А, 3B и 3D. Вивчали варіабельність МС-локусів третьої гомеологічної групи хромосом T. aestivum L., здійснили порівняння мінливості мікросателітів у дистальних та проксимальних областях хромосом, а також фізичне картування МС-локусів за допомогою делеційних, дітелосомних, нулітетрасомних ліній та провели порівняльний аналіз варіабельності мікросателітних локусів хромосом 3А, 3B і 3D.